2017
DOI: 10.1097/rli.0000000000000344
|View full text |Cite
|
Sign up to set email alerts
|

Histology and Gadolinium Distribution in the Rodent Brain After the Administration of Cumulative High Doses of Linear and Macrocyclic Gadolinium-Based Contrast Agents

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
202
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(229 citation statements)
references
References 52 publications
23
202
3
1
Order By: Relevance
“…Whereas several studies in animals have looked at gadoterate and gadobutrol in terms of Gd accumulation in the brain and other organs, comparatively few studies have evaluated gadoteridol after a prolonged off‐dose period. In one recent study aimed at investigating the differential effects on histology between macrocyclic and linear GBCAs, Lohrke et al found only minimally different levels of Gd in the brains of animals administered gadobutrol compared with animals administered gadoteridol (0.7 ± 0.4 vs. 0.5 ± 0.2 nmol Gd/g tissue, respectively; evaluation of significance not presented). Conversely, a more recent independent study by McDonald et al found higher median concentrations of Gd in brain tissue of gadobutrol‐injected rats than in brain tissue of gadoteridol‐injected rats (1.6 vs. 0 mg/g tissue, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas several studies in animals have looked at gadoterate and gadobutrol in terms of Gd accumulation in the brain and other organs, comparatively few studies have evaluated gadoteridol after a prolonged off‐dose period. In one recent study aimed at investigating the differential effects on histology between macrocyclic and linear GBCAs, Lohrke et al found only minimally different levels of Gd in the brains of animals administered gadobutrol compared with animals administered gadoteridol (0.7 ± 0.4 vs. 0.5 ± 0.2 nmol Gd/g tissue, respectively; evaluation of significance not presented). Conversely, a more recent independent study by McDonald et al found higher median concentrations of Gd in brain tissue of gadobutrol‐injected rats than in brain tissue of gadoteridol‐injected rats (1.6 vs. 0 mg/g tissue, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, McDonald et al further corroborated our findings in demonstrating markedly higher median concentrations of Gd also in the kidney, liver, and spleen of rats administered gadobutrol than in rats administered gadoteridol. Of note, however, is that whereas Lohrke et al allowed 8 weeks' recovery after the last GBCA administration before animal sacrifice, McDonald et al allowed only 7 days. However, this again points to a more rapid and efficient elimination mechanism for gadoteridol, possibly reflecting advantageous physicochemical properties.…”
Section: Discussionmentioning
confidence: 99%
“…36 In an additional study, after repeated high dosing in rats with normal renal function, NSF like macroscopic and microscopic lesions in the skin were only seen with gadodiamide. 37 These were not seen with gadopentetate dimeglumine and the 2 evaluated macrocyclic GBCAs, gadobutrol and gadoteridol. No histologic changes were observed with any agent in the brain.…”
Section: Recent Animal Investigationsmentioning
confidence: 99%
“…HIGH SIGNAL INTENSITY of deep cerebellar and deep brain nuclei on unenhanced T 1 ‐weighted images as well as changes of T 1 relaxometry values may reflect the presence of long‐term retained or deposited gadolinium in the brain in patients exposed to cumulative doses of gadolinium‐based contrast agents (GBCAs). In the cerebellum, the dentate nuclei (DN) and the cortex are the areas where gadolinium predominantly retains and/or accumulates …”
mentioning
confidence: 99%